Duas metades, uma existência: produção de masculinidades e feminilidades na Irmandade da Boa Morte e no Culto de Babá Egun - Conceição, Joanice Santos (2011)
This work is about death rituals and deals primarily with the questions of masculinities, femininities and performance in both Irmandade da Boa Morte (Sisterhood of the Good Death) and Sociedade Egungun (The Cult to the Ancestors). This is done taking into account two different aspects: one is how death is dealt with in the ancestor worship rituals and the other refers to the female invisibility and interdict on those rituals. The analysis stresses the elements that are associated with those three categories as well as the strategies used both to justify the keeping out of males and to destroy male domination. It endeavors to understand the symbolism that goes through the representation system of masculinity and femininity that takes place on the ritual sphere, mainly the sexual division and hierarchy on the Culto de Babá Egun. Asserting the opposite, the Irmandade da Boa Morte boasts female exclusivity. It must be said that both groups maintain concepts that diverge to those held on the West, since the Nago world vision holds that human life is lived in two plans, aiyê and orun. The former is the concrete, physical realm while the latter is the supernatural, abstract, endless world occupied by supernatural beings. Hence, this study maintains that both men and women perform masculine and feminine roles in order to ensure the practices of funeral rites along with keeping the power existing in the rituals. Both women and men use, albeit with different meanings, the Yoruba creation myth system to legitimize their discourses. On one hand, men justify their exclusion of females from the spaces where the mortuary rites are performed. On the other hand women use the same myths to explain how men changed from the subjugated position to become dominant and furthermore, subvert dominant masculinity when worshiping the ancestors spirits. The studied groups not only maintain Yoruba funeral rites but in addition carry out the leading roles . The empirical data jointly with the theory allows us to understand the contradictions present on the narratives of both men and women, facing the many forms of producing masculinity and femininity and opposing male supremacy. Studying the data resulted in understanding the duality within the system of believes of Irmandade da Boa Morte and Culto de Babá Egun practitioners go beyond their formal procedure and are present in their everyday lives together with the importance of all involved un the rituals